2003
DOI: 10.1097/00005176-200302000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Mesenterico-Left Portal Vein Bypass in Children With Congenital Extrahepatic Portal Vein Thrombosis: A Unique Curative Approach

Abstract: In accordance with the limited experience published by others, the authors' data confirmed the mesenterico-portal Rex shunt as the therapy of choice for children with EPVT. Furthermore, this report is the first to show that a hepatopulmonary syndrome can be abolished by mesenterico-portal Rex shunt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 13 publications
1
34
0
8
Order By: Relevance
“…Mack et al [17] and Chiu [18] showed that successful MPB improves fluid cognitive ability and reversed encephalopathy related to portosystemic shunting. Fuchs et al [19] reported the successful management, by MPB, of a patient with hepatopulmonary syndrome related to EPVO, which we have confirmed in 1 further case.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Mack et al [17] and Chiu [18] showed that successful MPB improves fluid cognitive ability and reversed encephalopathy related to portosystemic shunting. Fuchs et al [19] reported the successful management, by MPB, of a patient with hepatopulmonary syndrome related to EPVO, which we have confirmed in 1 further case.…”
Section: Discussionsupporting
confidence: 78%
“…Fuchs et al [19] showed in a small series (n = 7) with short follow-up (5-28 months) that the spleen size decreased in all patients post-MPB but normalized in only 1 case. In our series, the spleen size decreased in all patients, both clinically and radiologically, but returned to "normal-forage" in only 30%.…”
Section: Discussionmentioning
confidence: 95%
“…Other centers report that Ͻ50% of children with EHPVT can be treated with MLPVB based on the lack of an appropriate-sized intrahepatic portal vein, 13,14,41 which would suggest that we would identify equal or greater numbers of control subjects for our studies. However, that turned out to not be the case.…”
Section: Figurementioning
confidence: 99%
“…[11][12][13][14] Originally designed to correct acute portal vein thrombosis in liver transplant recipients, the operation entails using an autologous vein as a jump graft from the mesenteric vein to the well-developed left portal vein in the Rex recessus and has been called a mesoRex shunt. 15 Children with primary idiopathic EHPVT often have a small underdeveloped or atrophic intrahepatic portal venous system, which has caused some technical problems in performing MLPVB.…”
mentioning
confidence: 99%
“…Portal vein thrombosis is bypassed with an autologous vein graft (usually left internal jugular vein) in the MLPB procedure [4][5][6][7][8]. de Ville de Goyet et al [3] in their first case used cadaveric allograft, but graft thrombosis and loss occurred; thus, they started using autologous vein grafts.…”
Section: Discussionmentioning
confidence: 99%